Development of statistics teaching materials with a STEM approach to improve mathematical communication skills in online learning - Hadi, Sofwan; Rusdiana, Fendi Krisna (LP3M Universitas Islam Zainul Hasan Genggong, 2025)
This study aims to develop STEM-based Teaching Materials with a STEM approach to Online learning. Post-COVID-19 pandemic, online learning is a familiar form of activity, so post-pandemic learning and learning design must be developed, especially to measure students’ mathematical Communication skills. This study used the study and Development study methodology with the ADDIE Model. The sample in this study was 80 students. This study showed a significant difference of 0.44, which stated that using STEM teaching materials was better than regular learning in mathematical Communication skills. Two factors, namely ease of access to teaching materials and ease of repeating teaching materials, affect students’ Communication skills